2012
DOI: 10.1002/cncr.27786
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of 2 reduced‐intensity conditioning strategies for human leukocyte antigen‐matched, related allogeneic peripheral blood stem cell transplantation

Abstract: BACKGROUND:The optimal intensity of reduced-intensity conditioning (RIC) before allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains uncertain. METHODS: In this centrally randomized phase 2 study, the authors compared 2 different strategies of RIC. In total, 139 patients (median age, 54 years; range, 21-65 years) with hematologic malignancies underwent allo-HSCT from a human leukocyte antigen-identical sibling after conditioning combining fludarabine with either busulfan and rabbit antithymoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…In agreement with other reports, [18][19][20][21][22] we observed that the myeloablative conditioning regimen lacking ATG resulted in a higher incidence of aGVHD development. One may ask why the beneficial effect of ATG in reducing aGVHD does not translate into benefits in patient survival.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other reports, [18][19][20][21][22] we observed that the myeloablative conditioning regimen lacking ATG resulted in a higher incidence of aGVHD development. One may ask why the beneficial effect of ATG in reducing aGVHD does not translate into benefits in patient survival.…”
Section: Discussionsupporting
confidence: 93%
“…Despite their limitations, a limited number of comparative studies suggest that regimen intensity is directly associated with non-relapse mortality (NRM) and inversely associated with relapse, leading to equivalent survival rates regardless of regimen intensity. 17,23,24 One commonly used regimen is Flu/TBI2. Mature results show that almost half of the recipients completed transplant as outpatients and only 4% encountered graft rejection.…”
Section: Efficacy-is There An Ideal Conditioning Regimen?mentioning
confidence: 99%
“…The combination of fludarabine, an intermediate dose of intravenous busulfan and lowdose antithymocyte globulins is among the most popular RIC regimens used in Europe, particularly in France. [6][7][8][9] Nevertheless, relapse remains challenging after such regimens. [6][7][8][9][10][11] Therefore, attempts to intensify the RIC regimen without increasing nonrelapse mortality might be an attractive option in order to obtain better disease control while waiting for the immune graft-versus-leukemia effect.…”
Section: Introductionmentioning
confidence: 99%